A new species of Mecophilus (Geophilidae: Aphilodontinae), with the first report of the genus from the state of Rio de Janeiro, Brazil - Calvanese, Victor C.; Brescovit, Antonio D. (Zootaxa, 2022)
Mecophilus carioca n. sp. is described based on males and females recently sampled in the Parque Nacional de Itatiaia, and is the first record of the genus from the state of Rio de Janeiro, Brazil. The specimens were analyzed in both light microscopy and scanning electron microscopy, and photos and schematic illustrations are provided. The known distribution of the three species of Mecophilus are presented in a map.